A first transition series pseudotetrahedral oxynitride anion: synthesis and characterization of Ba(2)VO(3)N. - Clarke, S; Chalker, P; Holman, J; Michie, C; Puyet, M; Rosseinsky, M (2002)
Ammonolysis of reactive oxide precursors affords the vanadium(V) phase Ba(2)VO(3)N that is shown by X-ray and neutron powder diffraction and Raman spectroscopy to contain pseudotetrahedral VO(3)N(4-) anions. This is the first example of such species for the first transition series metals.